2022
DOI: 10.3390/life12101553
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant, Analgesic, Anti-Inflammatory, and Wound Healing Activities of Haplophyllum tuberculatum (Forsskal) A. Juss Aqueous and Ethanolic Extract

Abstract: Herbal extracts are part of the solution to the increased demand for organic health care products. Traditionally, the different extracts prepared from Haplophyllum tuberculatum (Forsskal) A. Juss (H. tuberculatum) have been widely used to treat a wide range of illnesses. The aim of this study is to evaluate the antioxidant, analgesic, anti-inflammatory, and wound healing potential of the aqueous (HTAE) and ethanolic (HTEE) extracts of this plant as well as identify its major phytochemical components using LC-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Briefly, our study confirmed previous findings reported by Boughalleb et al, [18] , Al-Saeghi et al, [28] Agour et al, [29] Sharifi-Rad et al, [30] Benchikha et al, [31] and Makhlouf-Gafsi et al [32] Generally, to assess the antioxidant potential of bioactive extracts, several factors are involved such as solvent polarity, extraction methods, plant matrix and especially phenolic compounds containing including caffeic acid, 4-feruloylquinic acid, flavonoids, alkaloids and carotenoids. [16,[33][34][35]…”
Section: Antioxidant Activitiessupporting
confidence: 93%
See 1 more Smart Citation
“…Briefly, our study confirmed previous findings reported by Boughalleb et al, [18] , Al-Saeghi et al, [28] Agour et al, [29] Sharifi-Rad et al, [30] Benchikha et al, [31] and Makhlouf-Gafsi et al [32] Generally, to assess the antioxidant potential of bioactive extracts, several factors are involved such as solvent polarity, extraction methods, plant matrix and especially phenolic compounds containing including caffeic acid, 4-feruloylquinic acid, flavonoids, alkaloids and carotenoids. [16,[33][34][35]…”
Section: Antioxidant Activitiessupporting
confidence: 93%
“…According to their various therapeutic activities including antioxidant, anti‐inflammatory, hypoglycemic, Alzheimer's disease and other brain dysfunctions, as well as prevention of cancer and cardiovascular diseases [50] . Generally, the highest number of phenolic acids was identified in H. tuberculatum (DE: 72.73 % and UAE: 70.00 %) and P. equisetiforme (DE:63.64 % and UAE: 70.00 %), the same outcomes were achieved by Mahmoudi et al., [19] and Agour et al [29] . Unlike, only 27.27 % of total standard compounds were identified in M. arvensis (DE).…”
Section: Resultsmentioning
confidence: 54%
“…We also obtained a stock solution of 2,2-diphenyl-1-picrylhydrazyl free radical (DPPH) in the same solvent, at a concentration of 2 × 10 −4 M. To 1.8 mL of DPPH solution was added 0.2 mL of each solution of the compounds 1 – 9 and we left the mixture in the dark for 30 min, followed by measurements of the absorbance at λ max 517 nm. We obtained the TAC values using Equation (3), which is a common way to assess the antioxidant activity [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Extracts rich in phenolic compounds from Diospyros mespiliformis , Haplophyllum tuberculatum, and Mangifera indica showed important antioxidant, anti-inflammatory, and antimicrobial activities when evaluated in different models of wound healing [ 106 , 107 , 108 ]. Rocha et al [ 109 ] evaluated the antioxidant, anti-inflammatory, and healing activities of Artemisia campestris L. hydrodistillation residual water and its essential oil, finding that the residual hydrodistillation water showed promising antioxidant and anti-inflammatory activities without causing toxicity in the macrophages and fibroblasts.…”
Section: Mechanisms Of Action Of the Natural Products In Wound Healingmentioning
confidence: 99%